1982
DOI: 10.1007/bf00039193
|View full text |Cite
|
Sign up to set email alerts
|

Selection for yield in small plots of spring wheat

Abstract: SUMMARYFour selection experiments were sown: single-row plots with single row-spacing (:::: 20 em), single-row plots with double row spacing (:::: 40 em), three-row plots and six-row plots both with single row-spacing (:::: 20 em). Selection entries were mimiced by 16 different varieties or advanced breeding lines, which were also sown in a yield trial. Each experiment was laid out as a 4-times replicated randomized block design. Row length was 2 m. Alley borders and border-rows of multiple-row plots were harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…the ratio of the expected genetic gain in 6RP when selection is based on the SRP performance to the expected response when selection is applied directly to the 6RP trial. The relative selection efficiency was estimated by , where r is the correlation coefficient between the genotypic means of the two trials and the broad sense heritability in the 6RP trial [15]. Correlation coefficients between 6RP genetic means and SRP genetic values obtained with the different models described above (the two-factor analysis of variance model, neighbouring covariate models or the producer-competitor model) were statistically compared using the bootstrap resampling technique [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…the ratio of the expected genetic gain in 6RP when selection is based on the SRP performance to the expected response when selection is applied directly to the 6RP trial. The relative selection efficiency was estimated by , where r is the correlation coefficient between the genotypic means of the two trials and the broad sense heritability in the 6RP trial [15]. Correlation coefficients between 6RP genetic means and SRP genetic values obtained with the different models described above (the two-factor analysis of variance model, neighbouring covariate models or the producer-competitor model) were statistically compared using the bootstrap resampling technique [8].…”
Section: Methodsmentioning
confidence: 99%
“…In these trials, interplot competition may lead to biased estimations of yield performances [9] and particularly to the overestimation of the value of aggressive genotypes. Several authors have noted very low or even no correlations between yields of genotypes in singlerow plots and their yield in larger plots due to competition [6,10,15].…”
Section: Introductionmentioning
confidence: 99%
“…The correlated gain formula is appropriate where one test is the standard for comparison for the other tests. The correlated gain expected in performance of selections in the multiple-harvest trial (M) when using the rapid tests (R) for evaluation was calculated using a formula modified from KRAMER et al (1982) as shown in equation (1) …”
Section: Methodsmentioning
confidence: 99%
“…KRAMER et al (1982) found that with spring wheat, . The relation between DOM yield (t/ ha) and height (cm) for sixteen cultivars averaged ha) and height (cm) for sixteen cultivars in control over Kes.…”
Section: -mentioning
confidence: 99%